Incidence of marginal zone lymphoma in the United States, 2001–2009 with a focus on primary anatomic site. (12th January 2014) - Khalil, Mohammad O.; Morton, Lindsay M.; Devesa, Susan S.; Check, David P.; Curtis, Rochelle E.; Weisenburger, Dennis D.; Dores, Graça M.
Summary The aetiology of marginal zone lymphoma (MZL) is purported to differ by anatomic site. While this is supported by clinical series of single MZL sites, no population‐based study has comprehensively assessed incidence patterns across sites. To gain insight into disease aetiology, we assessed MZL incidence by site using data from 18 U.S. Surveillance, Epidemiology and End Results (SEER) Program population‐based registries. We calculated age‐adjusted incidence rates (IRs) by sex, race, and calendar year. During 2001–2009, 4, 081 (IR = 5·7/1, 000, 000 person‐years) and 8, 821 (IR = 12·3) individuals were diagnosed with nodal MZL and extranodal MZL, respectively. The most common extranodal sites were stomach (IR = 3·8), spleen (IR = 1·6), eye/adnexa (IR = 1·4), and lung, skin, and salivary glands (IRs = 0·9–1·0). We observed distinct age‐specific patterns by MZL site, with IRs increasing steeply at younger ages and less prominently after mid‐life at several sites, except skin. Gender and racial/ethnic disparities were also apparent across sites. Between 2001–2005 and 2006–2009, MZL IRs decreased significantly for gastric (−15%) and soft tissue (−28%) sites, whereas IRs increased significantly for lung (18%), skin (43%), and kidney/renal pelvis (116%). In combination, our findings support the contention that MZL is characterized by aetiological heterogeneity across sites and susceptibility is probably influenced by intrinsic characteristics and environmental exposures.